Optimalisasi Peran Stakeholder dalam Mendukung Strategi Digital Marketing dan Meningkatkan Daya Saing Pelaku Program Pekarangan Pangan Lestari (P2L) - Umu Khouroh; Christina Sri Ratnaningsih; Bayu Rahayudi (University of Merdeka Malang, 2023)
This research was conducted to investigate the influence of digital marketing strategy on the competitiveness of P2L businesses, examine the mediating role of digital marketing performance in the relationship between digital marketing strategy and the competitiveness of P2L businesses and examine the role of Stakeholders in moderating the influence of digital marketing strategies on the competitiveness of P2L businesses. This research uses a quantitative approach with a type of explanation. The research sample consisted of managers/members of the P2L program group in Malang Regency. Data was collected through a survey method by sending questionnaires online to members of the P2L group and 62 respondents from 30 P2L groups participated in this research. Data analysis used the SEM-PLS method using the SmarPLS4 program. Research findings show that digital marketing strategy has a big impact on business competitiveness, but digital marketing performance does not mediate the relationship between digital marketing strategy and competitiveness. Other findings show that the involvement of higher education and government Stakeholders has a big impact and strengthens the implementation of digital marketing strategies in increasing competitiveness. In the context of this big role, P2L group managers/members should maximize digital platforms and need to increase Stakeholder involvement to strengthen competitiveness